Evaluasi faktor penentu kinerja UMKM: Peran kompetensi SDM, literasi keuangan, modal keuangan, dan modal sosial - Wahyuningrum, Tri; Wibowo, Purwo Adi (Nur Science Institute, 2025)
This study analyzes the influence of human resource (HR) competence, financial literacy, financial capital, and social capital on the performance of Jepara City micro, small, and medium enterprises (MSMEs). The population of this study was 160 members of the Kartini Mandiri Jepara MSME Association, with a sample of 106 respondents obtained through purposive sampling. The data collected were primary data through the distribution of questionnaires. The analysis method used was Partial Least Square (PLS) to test the relationship between variables. The results of the study indicate that HR competencies, financial literacy, and financial capital have a significant effect on MSME performance. Conversely, social capital does not affect MSME performance. These results show that access to financial resources is essential in improving business performance. These findings suggest that strategies to improve SME performance should focus on strengthening access to capital and financial management. Additionally, further efforts are needed to enhance the effectiveness of human resource competencies and financial literacy to contribute more significantly to SME performance.